Lessons from the Polish way of transformation - Woźniak, Michał Gabriel (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article compares the characteristics of state and market-driven coordination. It derives from them the need to return to capitalism. The author describes the role of the state in the process of market liberalization of the centrally planned economy, the dilemmas of state modernization, the problems emerging from the overstressed dynamics of the transition to the market. Against this background, the main features of Polish transformation have been described and the mistakes made have been identified. The author also answers the question of whether the choice of an alternative model of capitalism was possible than that proposed by the Washington consensus. The author postulates the use of the conclusions of the critical analysis of the Polish way of transformation in the new wave of reform of the economy and the functioning of the public sector in Poland.

W artykule porównano cechy koordynacji kierowanej przez państwo i rynkowej. Wywodzi się z nich konieczność powrotu do kapitalizmu. Autor opisuje rolę państwa w procesie urynkowienia nieprywatnej gospodarki centralnie planowanej, dylematy modernizacji państwa, problemy wyłaniające się ze zbyt forsownej dynamiki przejścia do rynku. Na tym tle wskazuje na główne cechy polskiej transformacji oraz popełnione błędy. Podjął również próbę odpowiedzi na pytanie, czy możliwy był wybór alternatywnego wzorca kapitalizmu niż postulowany przez konsensus waszyngtoński. Autor postuluje wykorzystanie wniosków płynących z krytycznej analizy polskiej drogi transformacji w nowej fali reformowania gospodarki i funkcjonowania sektora publicznego w Polsce.
Keywords: Polish economy; transformation; economic history; gospodarka Polski; transformacja; historia gospodarcza